Chaos Theory in Geomorphology - M .H. Ramesht (جغرافیا و توسعه, 2003)
The past three dicades can be considered as a period in which the fundamentals of scientific epistemology have been subjected to drastic revision.The dissemination of the general theory of systems in 1972, one year after the death of ludwing von Berthalanfi, the proposition of fuzzy logic by Zade, and the formulation of chaos theory in 1986 by Harison and Biswas all served to explode the myth that scientific thought was invulnerable. It is beyond dispute that the finalist and the dispensableness of causality characteristic of systems theory, the rejection by fuzzy logicians of scientific logic as a means of accounting for many multi-valued phenomena, and the non-conformity of a large number of events and modes of behaviour to scientific order in Chaos theory revealed one of the incontestable facts of our world: the inadequacy of scientific epistomology to analyse the behaviour and mechanism of certain phenomena. The endeavours made by researchers in scientific epistomology to endous events with systematicity have been predominantly geared towords gratifying the frenzy of predicting events and modes of behaviour. And this is exactly where chaos comes into the picture. For it points out the fact that, although such attempts have been fruitful in many cases, yet, not all events and modes of behaviour can be said to conform to scientific order, and that despite their predictability, linear predictions could hardly be regarded as a suitable solution in such cases. The concept of Chaos within geomorphology is primarily concerned with a systemic point of view and falls into the category of disequilibrium. And in the analyisis of many events and phenomena if this kind we wont be able to understand or explicate their underlying mechanisms without resorting to non-linear techiques, especially on a long time scale. This paper, which has resulted from the theoretical investigation of project based on the paraglicial sediment and glacial evidence on the Zagros-pishkoh to explain the elements of chaos theory and their compatibility with geomorphology.